Precautionary measures and European certificate of succession. Around the order of the Provincial Court of Barcelona of july 5, 2018 - Antón Juarez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The Auto of the Audiencia Provincial de Barcelona of July 5, 2018 is the first resolution on the European succesrion Regulation that is issued in Spain. This Auto emphasizes how the European Certificate of Succession is a valuable instrument of evidence in international mortis causa successions and how it can also affect the granting of precautionary measures.